Liquidity in the German corporate bond market: Has the CSPP made a difference? - Lena Boneva; Mevlud Islami; Kathi Schlepper (Deutsche Bundesbank, 2021)
The Eurosystem purchased exteuro178 billion of corporate bonds between June 2016 and December 2018 under the Corporate Sector Purchase Programme (CSPP). Did these purchases lead to a deterioration of liquidity conditions in the corporate bond market, thus raising concerns about unintended consequences of large-scale asset purchases? To answer this question, we combine the Bundesbank's detailed CSPP purchase records with a range of liquidity indicators for both purchased and nonpurchased bonds. We find that while the flow of purchases supported secondary market liquidity, liquidity conditions deteriorated in the long-run as the Bundesbank reduced the stock of corporate bonds available for trading in the secondary market.
Keywords: E52; F30; G12; 330; Corporate Bond Market; Central Bank Asset Purchases; Market Liquidity